Ethnopedagogy in Social Studies Learning Through The Approach of Local Wisdom Characters in Junior High School - Delva Yuliana (Social Studies Conference Proceedings, 2022)
Ethnopedagogy in Social Studies Learning with the concept of a character approach to local wisdom, sourced from several cultural diversity of local heritage. Local cultural values ​​based on these character approaches aim to increase students' awareness as part of education concerning this junior high school. It strengthens character for students to be responsible and maintain good social harmonization towards fellow social beings and daily life environment. This research uses a qualitative method with an ethnographic approach and classroom action research. According to Elliot, it is hoped that this research can show that students and educators in the school environment can preserve local wisdom in the school environment based on character education that encourages virtue values ​​such as cultural values ​​and norms. Customs in the community. Everything that supports these activities can be used as a source of social studies learning. The character approach in social studies learning in junior high school is expected to show results in students applying the values ​​of local wisdom in social studies learning both in the classroom and outside the community.